1995
DOI: 10.1680/macr.1995.47.171.167
|View full text |Cite
|
Sign up to set email alerts
|

A new technique for measuring the air permeability of near-surface concrete

Abstract: A non-destructive, rapid test capable of measuring the air permeability of in situ concrete is described. The technique is based on the application of a hard vacuum to the concrete surface. The rate of pressure recovery is recorded after the vacuum line is disconnected. The experimental results lead to an exponential pressure–time relationship similar to that obtained from analytical solution of Darcy’s equation. The air permeability of concrete can be simply expressed in terms of a vacuum decay parameter, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 6 publications
0
19
0
2
Order By: Relevance
“…Using CEM I grouts, Dewaele et al [9] obtained permeability decrease of several orders of magnitude after carbonation (by injection under pressure of CO 2 -rich water). Claisse et al [6] carbonated CEM I concretes (5% CO 2 ) and measured significant increase in the so-called impermeability index [18] indicating a fall in permeability. In the same way Song and Kwon [19] carbonated two CEM I concretes and found that the permeability coefficient of the carbonated concretes was three times less than that of the non-carbonated ones.…”
Section: Introductionmentioning
confidence: 99%
“…Using CEM I grouts, Dewaele et al [9] obtained permeability decrease of several orders of magnitude after carbonation (by injection under pressure of CO 2 -rich water). Claisse et al [6] carbonated CEM I concretes (5% CO 2 ) and measured significant increase in the so-called impermeability index [18] indicating a fall in permeability. In the same way Song and Kwon [19] carbonated two CEM I concretes and found that the permeability coefficient of the carbonated concretes was three times less than that of the non-carbonated ones.…”
Section: Introductionmentioning
confidence: 99%
“…MC refers to the moisture cured concrete, under which condition additional moisture was present in the concrete and no significant drying occurred from the surface in the whole curing period. The moisture content in the surface region was sufficient to yield low permeability (12,14). With respect to SC, concrete was sealed after 3 day water curing.…”
Section: Determination Of Steady-state Flow Rate Under Two Pressure Hmentioning
confidence: 99%
“…The second approach is to remove moisture from the sample by certain pre-conditioning methods. Dhir et al (12) suggested that vacuum dewatering could be used to eliminate the influence of moisture on results. Schonlin and Hilsdorf (13) used a hot air gun to dry out the moisture around test area prior to measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a high water pressure must be applied to obtain measurable flows, which can damage the studied medium. Insitu tests have also been developed (Claisse et al, 2003;Figg 1973;Basheer et al, 1994;Dhir et al, 1995). A number of laboratory based tests have been developed to measure the gas permeability of concrete and mortars, including the Cembureau test (Verdier and Carcassès, 2002;Kollek, 1989;Abbas et al, 1999).…”
Section: Introductionmentioning
confidence: 99%